Growth response of lettuce plants to the application of NASA liquid organic fertilizer and cow manure - Suci Septrianda; Muhammad Ammar (Research Center for Suboptimal Lands (PUR-PLSO), Universitas Sriwijaya, 2025)
Lettuce (Lactuca sativa L.) was a leafy vegetable that has high economic value in Indonesia and provides health benefits to consumers. The use of organic fertilizers is deemed more optimal than inorganic fertilisers due to the potential of inorganic fertilizers to cause soil damage and environmental pollution through chemical residues and land productivity reduction. The study aimed to evaluate the effects of using NASA liquid organic fertilizer and cow manure on the growth and yield of lettuce plants. The study used a Randomised Block Factorial Design with two factors: cow manure with four treatment levels and NASA liquid organic fertiliser with three treatment levels. The results showed that chicken manure had a significant effect on plant height, leaf area, leaf dry weight, and stem fresh weight at 28 days after planting (DAT), while NASA liquid organic fertilizer had no significant effect on all parameters except plant height at 7 DAT. Higher doses of chicken manure (S2 and S3) contributed to the increase in dry weight and fresh weight of leaves. Application of NASA liquid organic fertilizer at a dose of 4 ml/L (N2) showed a better response in supporting plant vigor than others. In addition, the highest plant fresh weight was obtained in the combination of S3 and N2 treatments, indicating a synergistic effect between the two types of organic fertilizers. High a dose of chicken manure (S3 = 900 g) can negatively affect growth by lowering soil pH and causing too acidic conditions that are not optimal for plants.